Habituation of Kaheman Rice in Building Students' Character (Case Study at SMPN 2 Campaka) - Suharyanto H Soro; Nana Herdiana Abdul Rahman; Feby Filga Cantika; Siti Nuraeni (Global Education Journal, 2026)
This research is based on the challenges of moral degradation and empathy crises among the younger generation due to digital disruption, as well as the gap between character education policies and practical realities in the field that still tend to be cognitive. This study aims to analyze the implementation of the "Beas Kaheman" habituation program as a form of revitalization of Sundanese local wisdom (perelek) in building the character of mutual cooperation, empathy, and religiosity in students, the researcher uses a case study approach with a qualitative type of research. Data was collected through methods, participatory observations, in-depth interviews with principals, teachers, and students, and documentation in the form of progress reports on the collection of Beas Kaheman results. The selection of samples in the study was carried out by purposive sampling. The data analysis technique follows the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing and verification. The results of the study showed that: (1) The implementation of Beas Kaheman was carried out in a structured manner every Thursday (in conjunction with the Nyanding Wawangi program), students voluntarily brought a handful of rice to be distributed to those in need. (2) This program can or succeeds in internalizing the main character values, namely social care (empathy), mutual cooperation, religiosity, and responsibility. (3) There is a positive transformation in student consciousness, from motivation that was initially instructional to intrinsic motivation (self-awareness) which is characterized by consistency of participation. (4) The main supporting factors are the example of teachers and parental support, while the inhibiting factors include limited storage facilities and lack of communication intensity with some parents. This study concludes that habituation based on local wisdom is effective as a concrete model of character education in schools.